Japanese Comic Strips in Increasing Writing Learning Achievement - Robihim, Robihim; Thamrin, Muhammad (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this study was to determine the effect of using Japanese comic strip media on students' writing skills. This study used a quasi-experimental method with a one-group pretest and posttest experimental design. The study was conducted in two classes (60 students) who received writing courses in the even semester of the 2023-2024 academic year. The data collection process used documents, observations and tests. The data analysis technique used a two-sample paired t-test. The test results showed t-stat <t-table (-49.4457 <2.0009), meaning that the use of Japanese comic strip media had a significant effect on students' Japanese writing skills. The pre-test results concluded that the high error rate was in the aspects of organization, logical development of ideas and grammar. However, the post-test results showed that the error rate was very small and below 30%. The results of the study have implications for the development of comic strip media as a tool for learning to write Japanese and students have also become familiar with Japanese culture from stories in comics